Prevalence of vitamin d deficiency and its correlation with anthropometric measurements in neonates in a tertiary care center: a cross sectional study - Anbalagan, Ashvini; Aswathaman, Nalini; Raghupathy, N. S. (International Journal of Contemporary Pediatrics, 2021)
Background: Globally hypovitaminosis D is highly prevalent among all population unsparing pregnant mothers. Maternal hypovitaminosis has negative implications on growing fetus. In India, only limited data is available on prevalence of neonatal vitamin D level. Hence this study was done to estimate the prevalence of cord blood vitamin D levels and its relation with anthropometric measurements in newborns. Methods: A cross sectional study was conducted in a tertiary care center on 30 newborns. Cord blood 25 OHD levels and anthropometric measurements were taken. Data were analyzed statistically. Results: Among 30 newborns, 10%, 43% and 46% of babies had vitamin D deficiency (<12 ng/ml), insufficiency and sufficiency respectively. 23% were low birth weight. 43% of low-birth-weight babies had statistically significant (p value<0.0001) hypovitaminosis D. No correlation found between vitamin D status and other anthropometric measurements. Conclusions: Prevalence of hypovitaminosis D has negative implications on birth weight which needs further studies.